Exploring the mechanism of citric acid for treating glucose metabolism disorder induced by hyperlipidemia. Issue 12 (20th September 2022) - Yadikar, Nigary; Ahmet, Aygul; Zhu, Jinfang; Bao, Xiaowei; Yang, Xiaojun; Han, Haixia; Rozi, Parhat
Abstract: Citric acid is a crucial organic in our daily life. The effect and mechanism of citric acid on glucose metabolism disorder induced by hyperlipidemia were explored by hyperlipidemic rat models which were established and treated with Xuezhikang and citric acid for 40 days. The results showed that citric acid significantly decreased liver index and reduced levels of triglyceride, total cholesterol and low‐density lipoprotein cholesterol, while increasing high‐density lipoprotein cholesterol. And citric acid observably decreased blood glucose and insulin resistance index, as well as increasing insulin sensitivity. Meanwhile, citric acid dramatically down‐regulated mRNA and protein expression levels of glucose‐6‐phosphatase (G‐6‐Pase) ( p < .01) and up‐regulated those of glucose transporter 4 (GLUT‐4) ( p < .01). And significantly increased the contents of acetic, propionic and butyric acids ( p < .01). These findings suggest that citric acid can regulate blood lipid levels in hyperlipidemic rats, reduce the resistance induced by hyperlipidemia, and improve insulin sensitivity. Practical applications: These findings suggest that citric acid can regulate blood lipid levels in hyperlipidemic rats, reduce the resistance induced by hyperlipidemia, and improve insulin sensitivity. and provide a theoretical basis for the application of citric acid in diseases related to glucose metabolism disorders. Abstract : Citric acid decreased liver index, HDL‐C blood, glucose and insulin resistance index, while reduced levels of TG, TC and LDL‐C. Citric acid down‐regulated mRNA and protein expression levels of G‐6‐Pase, while up‐regulated mRNA and protein expression levels of GLUT‐4. Citric acid increased the contents of acetic, propionic and butyric acids.